Encyclopaedia of physical education and sports Vol.4 Growth and development of physical education - Sharma, Bela Rani (ed); Kaushik, Vijaya (ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
Objectives of physical education